2002
DOI: 10.1177/146642400212200213
|View full text |Cite
|
Sign up to set email alerts
|

Audit of primary care angina management in Sandwell, England

Abstract: This audit aimed to assess the identification and treatment of coronary risk factors, lifestyle advice given and use of drug therapy, among patients with angina in Sandwell. It was designed to help general practices evaluate their angina management, and highlight areas where practice could be improved. Criteria were based on Sandwell's published angina audit and local clinical guidelines. Each participating practice was asked to identify all patients with angina, from which a 10% sample was randomly selected. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…8Y15 Most patients identified correct symptoms to treat with SLNTG, and no incorrect symptoms were included, despite concerns raised in previous studies. 11,12 Patients were also well informed regarding the administration methods, dosage, timing, and sequence and that the SLNTG could expire. 9,13,14 However, notable knowledge deficits occurred in relation to the use of SLNTG to prevent angina symptoms in stable angina, which has been noted in the literature.…”
Section: Slntg Instruction and Knowledgementioning
confidence: 99%
See 2 more Smart Citations
“…8Y15 Most patients identified correct symptoms to treat with SLNTG, and no incorrect symptoms were included, despite concerns raised in previous studies. 11,12 Patients were also well informed regarding the administration methods, dosage, timing, and sequence and that the SLNTG could expire. 9,13,14 However, notable knowledge deficits occurred in relation to the use of SLNTG to prevent angina symptoms in stable angina, which has been noted in the literature.…”
Section: Slntg Instruction and Knowledgementioning
confidence: 99%
“…8,9,13 Patients may also overgeneralize the symptoms they treat, using SLNTG inappropriately for multiple symptoms such as palpitations or dizziness. 11,12 On the other hand, most patients are reported to be aware of important safety requirements such as dosing and body position, 9,11,13,14 but are less aware of other safety requirements such as storage, prophylactic use, and when to seek medical assistance. 8,11,14,15 Several limitations were evident in the literature related to SLNTG knowledge in CAD patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…31 Ethnic minority patients are significantly less likely to receive advice on smoking cessation. 32 Like the white European population, studies find that The introduction of pay-for-performance incentives in UK primary care has been shown to be associated with better and more equitable management of CHD across ethnic groups, 36 and general practices with a higher proportion of south Asian patients have been reported as having higher rates of coronary angiography. 37 In populations already selected for coronary angiography, south Asians were also not inequitably managed in terms of prescription medication, 38 while the prognosis of coronary disease is equitable when comparing south Asians and white patients who have presented with angina.…”
Section: Prevalence Of Smokingmentioning
confidence: 99%
“…4 However, guidelines only have limited impact on (changing) a physician's routine practice. 5,6 Studies in other countries have shown that the medical care of patients with stable angina is often suboptimal [7][8][9][10][11] and it seems legitimate to assume that the situation is not different in the Netherlands. A Dutch study, for example, showed that only 51% of patients with AP diagnosed by GPs were prescribed aspirin.…”
mentioning
confidence: 99%